CEO Power, CEO Founder, CEO Financial Expertise, CEO Ownership, CEO Tenure on Bank Performance in Indonesia - Hakim, Luqman; Tantri, Mitsalina (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this research is to examine the influence of the personal characteristics of the chief executive officer (CEO) on the performance of commercial banks in Indonesia. In addition, it also analyzes the nonlinear relationship of CEO power, CEO founder, CEO financial expertise, CEO ownership, and CEO tenure to bank performance. A balanced panel data approach has been used in this study. In particular, fixed effect estimation techniques were used to examine the relationship between CEO power, CEO founder, CEO financial expertise, CEO ownership, CEO tenure, and bank performance from 2015 to 2021. so that the total amount of data processed is 3,780 data. The writer finds that the professional qualifications of CEOs are in bank performance. In addition, the impact of the CEO's financial expertise and tenure was positive and significant on performance. And the influence of CEO power, CEO founder, and CEO ownership was seen to be negative and not crucial to bank performance. CEO tenure is beneficial for bank performance. Experienced CEO contributes to higher bank performance. The results are robust across various bank performance proxies and control variables. This study provides insight into the policy regulators and policymakers entrusted with appointing CEOs in banks in light of the ongoing regulatory reforms in Indonesia. This study is one of the early studies examining the relationship between CEO power, CEO founding, CEO financial expertise, CEO ownership, CEO tenure, and bank performance from an emerging economy perspective. It also expands on existing studies to consider both state-owned and private banks operating in Indonesia.